2001
DOI: 10.1104/pp.125.2.877
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Coordinately and Differentially Regulates Growth- and Stress-Related Gene Expression via a Complex Signal Transduction Network and Multiple Control Mechanisms

Abstract: In plants, sugars are required to sustain growth and regulate gene expression. A large set of genes are either up-or down-regulated by sugars; however, whether there is a common mechanism and signal transduction pathway for differential and coordinated sugar regulation remain unclear. In the present study, the rice (Oryza sativa cv Tainan 5) cell culture was used as a model system to address this question. Sucrose and glucose both played dual functions in gene regulation as exemplified by the up-regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(98 citation statements)
references
References 79 publications
(58 reference statements)
5
85
0
2
Order By: Relevance
“…Moreover, such adjustments should be closely coordinated to maintain harmonious physiology (Koch et al, 2000). Many stress-related genes were found to be coordinately expressed under sugar starvation, either via hexokinase-dependent or independent pathways in rice (Ho et al, 2001). Such sugar regulated expression of many stress-related genes suggested two signaling cascades of the nutritional and environmental stress would be converged at certain point of the pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, such adjustments should be closely coordinated to maintain harmonious physiology (Koch et al, 2000). Many stress-related genes were found to be coordinately expressed under sugar starvation, either via hexokinase-dependent or independent pathways in rice (Ho et al, 2001). Such sugar regulated expression of many stress-related genes suggested two signaling cascades of the nutritional and environmental stress would be converged at certain point of the pathway.…”
Section: Introductionmentioning
confidence: 99%
“…3B). Previously, Ho et al (2001) found that treatment of 2-deoxyglucose up to 0.5 mM was toxic to suspension cultured rice cells. However, no significant deterioration of total RNA isolated from 2-deoxyglucose treated cells was observed in our examination of ethidium bromide staining of rRNA.…”
mentioning
confidence: 99%
“…Sugars modulate nearly all fundamental processes throughout the entire life cycle of plants, including embryogenesis, germination, growth, development, reproduction, senescence, and responses to diseases and environmental stimuli (Smeekens, 2000;. In general, sugars upregulate genes involved in biosynthesis, transport, and storage of reserves and cell growth and downregulate those associated with photosynthesis, reserve mobilization, and response to stresses (Graham, 1996;Koch, 1996;Ho et al, 2001). Studies with Arabidopsis thaliana and rice (Oryza sativa) have revealed intimate interaction between sugar and plant hormones, environmental stimuli, and metabolic signaling pathways (Sheen et al, 1999;Gibson, 2000;Smeekens, 2000;Coruzzi and Zhou, 2001;Gazzarrini and McCourt, 2001;Rolland et al, 2002Rolland et al, , 2006Hong et al, 2003;Chen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…30) The signal transduction pathways in which sugars function are complex, with multiple mechanisms of regulation. 31,32) In an attempt to investigate the sugar response in plants, we isolated from rice embryos cDNAs that are either up-or down-regulated by sugars using cDNA microarray technology. We characterized a novel cDNA, OsSUR1, that is up-regulated by sugar and Fig.…”
Section: Discussionmentioning
confidence: 99%